A universalização da internet e os direitos humanos. - Pirani, Mateus Catalani (2017)
Interdisciplinary study in applied Social Sciences area, establishing relations between Human Rights, Digital and International developed as master¿s thesis, the present work brings qualitative research on the universalization of the Internet, with Human rights approach in the current world-wide scenery. The appearance of a technological society and the impacts that the Internet imposes on an international scenery, they bring questions connected with the human rights. From the Internet it is possible to create new levels of relationship, which does so that it stops being a tool of studies and starts to be used like a communication way between the persons. Being so, the reason to be of this work results from the necessity of which this communication is within reach of all, in other words from his universalization. Such universalization must be understood as it forms one of human rights realization, be in function of the freedom of expression, of the right to the information or of other rights connected with the human dignity. Human rights off-line must be also online proteges. Besides, the universalization of the Internet can be understood like a human right in herself, in the direction of avoiding that a digital exclusion takes place in current social contemporary fact. The thematic seal in the analysis of the Internet like a social phenomenon, as well as like his relationship with rights, in order that there is drawn a view that allows the defense of the universalization of the Internet while it leaves from the outline of the human rights.